Retrieval Probabilities of Secondary Control Reserve within Systems with a High Share of Renewable Energies - Philipp Hanemann; Thomas Bruckner (Universität Leipzig, Institut für Infrastruktur und Ressourcenmanagement (IIRM), 2016)
In this paper, empirically determined retrieval probabilities for control power are investigated. Since there is a continuous need for balancing unscheduled deviations of supply and demand, control power is of very high importance for the stability of the power system. Systems that are characterized by a high share of intermittent energy feed-in are especially effected. Since the market conditions have an influence on bidding behavior, those who are participants in the balancing market have an interest in gaining information about the activation of control power. Though the magnitudes have been changing over the last years, there are clear time dependent patterns.
Keywords: 330; control power; retrieval probabilities; frequency control; power system economics